HOMERO. Ilíada. Tradução de Odorico Mendes, prefácio e notas verso a verso de Sálvio Nienkötter. São Paulo/ Campinas: Ateliê Editorial/UNICAMP, 2008. (912 p.) ISBN 9788574803937 / 9788526807952 (Nuntius Antiquus, 2009)
.